STOCK RETURN EFFECT DURING COVID-19: EVIDENCE FROM INDONESIA - Lina Lina; Hesniati Hesniati; Robin Robin; Ferdinand Nainggolan (UNIVERSITAS INDRAPRASTA PGRI, 2022)
This paper evaluated the impact of Covid-19 in Indonesia. The total samples used in this observation were 140,864 samples from Indonesia, collected from March 05, 2020, until December 30, 2020. The regression used was STATA 13.1, and the independent variable was the stock return. Meanwhile, the other variables used to measure the impact of Stock return during Covid-19 are Trading volume, Exchange rate, and Friday. The result revealed that Stock returns in Indonesia were negatively affected by Covid-19, the impact being carried away from the investors’ uncertainty and anxiety about Covid-19. On the other hand, trading on Friday makes investors less suffering from negative returns.